2021
DOI: 10.1681/asn.2020121694
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Body Mass Index and Metabolic Parameter Variabilities in Predialysis CKD: A Nationwide Observational Cohort Study

Abstract: BackgroundThe association between variabilities in body mass index (BMI) or metabolic parameters and prognosis of patients with CKD has rarely been studied.MethodsIn this retrospective observational study on the basis of South Korea’s national health screening database, we identified individuals who received ≥3 health screenings, including those with persistent predialysis CKD (eGFR <60 ml/min per 1.73 m2 or dipstick albuminuria ≥1). The study exposure was variability in BMI or metabolic parameters until ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…In the current study, following our previous study [ 12 ], we first identified non-dialysis-dependent CKD patients based on estimated glomerular filtration rate (eGFR) and dipstick urine albumin results measured in consecutive health screenings. After determining the visit-to-visit BP variability of the study population, the association between BP variability and the risk of dementia, identified from the claims database, was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the current study, following our previous study [ 12 ], we first identified non-dialysis-dependent CKD patients based on estimated glomerular filtration rate (eGFR) and dipstick urine albumin results measured in consecutive health screenings. After determining the visit-to-visit BP variability of the study population, the association between BP variability and the risk of dementia, identified from the claims database, was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…We first screened individuals who had received baseline health screenings from 2013 to 2014. As three or more health screenings were necessary to determine visit-to-visit BP variability, those who had two or more health screenings before the baseline visits were included [ 12 ]. After excluding those with missing information for any collected variable, the target CKD population included those with persistent eGFR <60 mL/min/1.73 m 2 or dipstick albuminuria ≥1+ during the exposure assessment period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations